Antagonistic effect of natural habitat conversion on community adjustment to climate warming in nonbreeding waterbirds. Issue 4 (15th April 2020) - Gaget, Elie; Galewski, Thomas; Jiguet, Frédéric; Guelmami, Anis; Perennou, Christian; Beltrame, Coralie; Le Viol, Isabelle
Abstract: Although the impacts of climate and land‐use changes on biodiversity have been widely documented, their joint effects remain poorly understood. We evaluated how nonbreeding waterbird communities adjust to climate warming along a gradient of land‐use change. Using midwinter waterbird counts (132 species) at 164 major nonbreeding sites in 22 Mediterranean countries, we assessed the changes in species composition from 1991 to 2010, relative to thermal niche position and breadth, in response to regional and local winter temperature anomalies and conversion of natural habitats. We observed a low‐level, nonsignificant community adjustment to the temperature increase where natural habitat conversion occurred. At the sites affected by natural habitat conversion, the relative increase of warm‐dwelling species in response to climate warming was 6 times lower and the relative species decline was 3 times higher than in the sites without natural habitat conversion. We found no evidence of community adjustment to climate warming when natural habitat conversion was >5% over 15 years. This strong negative effect suggests an antagonistic interaction between climate warming and habitat change. These results underline the importance of habitat conservation in community adjustment to climate warming. Abstract : Article impact statement : Waterbird communities do not adjustment to climate warming when natural area conversion is >5% over 15 years. Abstract : Efecto Antagonista de la Conversión de Hábitats Naturales sobre el Ajuste Comunitario ante el Calentamiento Climático en Aves Acuáticas No Reproductoras Resumen: Aunque el impacto de los cambios del clima y del uso de suelo sobre la biodiversidad está ampliamente documentado, los efectos conjuntos de estos cambios todavía no están entendidos del todo. Evaluamos cómo las comunidades no reproductoras de aves acuáticas se ajustan al calentamiento climático a la par de un gradiente de cambio de uso de suelo. Usamos conteos de aves acuáticas (132 especies) realizados en pleno invierno en 164 sitios no reproductores importantes en 22 países mediterráneos, evaluamos los cambios en la composición entre 1991 y 2010 en relación a la posición termal y a la amplitud del nicho en respuesta a las anomalías en la temperatura invernal local y a la conversión de hábitats naturales. Observamos un ajuste comunitario no significativo de bajo nivel al incremento de la temperatura en los lugares en donde ocurrió la conversión del hábitat natural. En los sitios afectados por la conversión del hábitat natural, el incremento relativo de las especies de hábitats cálidos como respuesta al calentamiento climático fue seis veces más bajo y la declinación relativa de especies fue tres veces más alto que en los sitios sin conversión del hábitat natural. No encontramos evidencias del ajuste comunitario al calentamiento climático cuando la conversión del hábitat natural fue >5% durante 15 años. Este efecto negativo pronunciado sugiere una interacción antagonista entre el calentamiento climático y el cambio del hábitat. Estos resultados remarcan la importancia que la conservación del hábitat tiene para el ajuste comunitario ante el calentamiento climático. 摘要: 虽然气候和土地利用变化对生物多样性的影响已有许多研究, 但这二者的共同作用仍不甚清楚。为此, 我们评估了非繁殖水鸟群落如何在一系列土地利用变化梯度上对气候变暖做出的响应。我们利用 22 个地中海国家 164 个主要非繁殖地隆冬时期 132 种水鸟数量的数据, 评估了 1991 年至 2010 年间水鸟群落的物种组成相对于热生态位位置和宽度的变化, 作为对局部地区和当地冬季温度异常及自然生境转换的响应。我们观察到在发生自然生境转换的地区, 水鸟群落对温度升高做出了低水平、不显著的响应。在受到自然生境转换影响的位点, 适应温暖环境的物种响应气候变暖而发生的相对物种增加比没有自然生境转换的位点低六倍, 而相对物种减少则三倍于未受自然生境转换影响的位点。在 15 年来自然生境转换超过 5% 的地区, 没有证据显示群落可以适应气候变暖。这种强烈的负面影响表明气候变暖和生境变化之间可能存在拮抗互作。这些研究结果突显了生境保护在群落适应气候变暖中的重要性。【翻译: 胡怡思; 审校: 聂永刚】